Topografia ficcional: a construção do espaço nos manuscritos de Osman Lins - Francisco José Gonçalves Lima Rocha (Estudos de Literatura Brasileira Contemporânea)
In the construction of the narrative space of his final, unfinished novel, A cabeça levada em triunfo, Osman Lins operates both verbal, with notes planning, as iconically, through drawings. Will try to show that the author’s purpose is to clarify the topography of the work, because it establishes and harmonizes the technical functions - ie, like space, says Osman Lins, “frame” the character – and symbolic means, ie. how the space reflects, like all other elements of the work, the questioning of the head-body dichotomy.